Mudarabah capital from multiple investors in investment accounts: scope and consequences in Islamic law - Sadique, Muhammad Abdurrahman (2013)
Investment accounts offered by Islamic financial institutions manifest features developed through a convergence of the principles of shirkah and mudārabah. A number of partners pooling their funds together for running a business operation is possible under shirkah. In the case of mudārabah, schools of Islamic law have recognised the validity of several parties jointly investing funds with a common mudārib through a single contract. Where several parties invest with a single mudārib, such investment should take place on a single occasion, so that the tenure of mudārabah could commence with regard to all deposits at the same time. Where the mudārib accepts investments from different individuals through individual contracts, the majority of schools require that the business of each capital be managed separately. The restriction is due to fundamental anomalies that may result from mixing different capitals. However, Hanafi jurists appear to have allowed the mudārib to mix funds of different investors together with the permission of the investors. This could indicate permission for mixing funds invested at different stages when overall permission had been obtained. Similarly, mixing mudārabah funds with funds of the mudārib could be valid according to the majority of schools with express permission of investors. Thus the Hanafi position appears to uphold the validity of mixing funds belonging to different investors who had invested at varying points of time, as practised in investment accounts.